PELATIHAN TEACHING GAMES FOR UNDERSTANDING MODEL BAGI GURU PENDIDIKAN JASMANI DI YAYASAN AL-ASHRIYYAH NURUL IMAN ISLAMIC BOARDING SCHOOL - samsudin; Moch. Asmawi; Sudradjat Wiradihardja; Shela Ginanjar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2024)
The purpose of this community service is to assist the needs of physical education teachers in developing Teaching Games For Understanding models that will be used in physical education subjects as well as to improve the implementation of learning. The research methodology used is Experimental Designs, the design used is One Sample Pretest-Posttest Design. The population was 35 physical education teachers at SD – SMA physical education teachers at the Al-Ashriyyah Nurul Iman Islamic Boarding School Foundation, Bogor, West Java, so the sample was taken using the Total Sampling technique. The instrument uses a questionnaire related to Physical Education Teachers' Teaching Preparation Indicators. The results show that the Teaching Games For Understanding training model that has been implemented at the Al-Ashriyyah Nurul Iman Islamic Boarding School Foundation is able to have a positive influence on the Teaching Preparation Indicators for Physical Education Teachers in order to achieve the learning objectives expected by the curriculum in force in Indonesia. Keywords: Teaching Games For Understanding Model; Guru Pendidikan Jasmani; Yayasan Al-Ashriyyah Nurul Iman Islamic Boarding School Abstrak Tujuan dari pengabdian kepada masyarakat ini untuk membantu kebutuhan guru pendidikan jasmani dalam menyusun Teaching Games For Understanding model yang akan digunakan pada mata pelajaran pendidikan jasmani serta untuk perbaikan dalam pelaksanaan pembelajaran. Metodologi penelitian yang digunakan adalah Experimental Designs, adapun desain yang digunakan One Sample Pretest-Posttest Design. Populasi adalah guru pendidikan jasmani di guru pendidikan jasmani SD – SMA di Yayasan Al-Ashriyyah Nurul Iman Islamic Boarding School, Bogor, Jawa Barat sebanyak 35 orang maka sampel diambil menggunakan teknik Total Sampling. Instrument menggunakan Angket yang berkaitan dengan Indikator Persiapan Mengajar Guru Pendidikan Jasmani. Hasil menunjukan bahwa pelatihan Teaching Games For Understanding model yang telah dilaksanakan di Yayasan Al-Ashriyyah Nurul Iman Islamic Boarding School mampu memeberikan pengaruh yang positif terhadap Indikator Persiapan Mengajar Guru Pendidikan Jasmani guna mencapai tujuan pembelajaran yang diharapkan oleh kurikulum yang berlaku di Indonesia. Kata Kunci: Teaching Games For Understanding Model; Guru Pendidikan Jasmani; Yayasan Al-Ashriyyah Nurul Iman Islamic Boarding School